Leaching as a pretreatment process to complement torrefaction in improving co-firing characteristics of Jatropha curcas seed cake - Madanayake, Buddhike Neminda; Gan, Suyin; Eastwick, Carol; Ng, Hoon Kiat (Springer Verlag, 2016)
The presence of certain inorganic elements in biomass causes issues such as slagging, fouling and corrosion when co-firing with coal for power generation. In this work, the efficacy of leaching to remove these elements from Jatropha curcas seed cake was investigated. Leaching of both untorrefied and torrefied seed cakes was carried out in Milli-Q water at temperatures of 20, 35 and 50 °C. At 20 °C, the two critical elements, potassium and chlorine, decreased by as much as 85 and 97 %, respectively. Leaching at higher temperatures was only beneficial for the more intensely torrefied biomass, since they were more resistant to leaching. The electrical conductivity and ion content of the leachates were measured, as were the inorganic elemental content, dry ash content, volatile matter content and higher heating value (HHV) of the solid seed cake. A secondary benefit of the leaching was an increase in the HHV by up to 10 %.